English language teacher education in changing times perspectives, strategies, and new ways of teaching and learning - England, Liz; Stein, Lía D. Kamhi-; Kormpas, Georgios (Routledge, 2023)
"This volume addresses challenges that the field of English language teacher edu- cation has faced in the past several years.The global pandemic has caused extreme stress and has also served as a catalyst for new ways of teaching, learning, and leading. Educators have relied on their creativity and resiliency to identify new and innovative teaching practices and insights that inform the profession going forward. Contributors describe how teacher educators have responded to the specific needs and difficulties of educating teachers and teaching second language learners in challenging circumstances around the world and how these innova- tions can transform education going forward into the future. Paving the way for a revitalized profession, this book is essential reading for the current and future generations of TESOL scholars, graduate students, and professors." (Verlagsinformation)
Keywords: Lehrerbildung; Englischunterricht